Doxycycline-Coated Silicone Breast Implants Reduce Acute Surgical-Site Infection and Inflammation. Issue 5 (November 2020) - Baker, Jennifer E.; Seitz, Aaron P.; Boudreau, Ryan M.; Skinner, Mitchell J.; Beydoun, Ahmed; Kaval, Necati; Caldwell, Charles C.; Gulbins, Erich; Edwards, Michael J.; Gobble, Ryan M.
Abstract : Background: Surgical-site infection after implant-based breast reconstruction remains a leading cause of morbidity. Doxycycline is an antibiotic used to treat soft-tissue infections. The authors hypothesize that doxycycline-coated breast implants will significantly reduce biofilm formation, surgical-site infection, and inflammation after bacterial infection. Methods: Pieces of silicone breast implants were coated in doxycycline. In vitro studies to characterize the coating include Fourier transmission infrared spectroscopy, elution data, and toxicity assays ( n = 4). To evaluate antimicrobial properties, coated implants were studied after methicillin-resistant Staphylococcus aureus (MRSA) and Pseudomonas aeruginosa inoculation in vitro and in a mouse model at 3 and 7 days ( n = 8). Studies included bacterial quantification, cytokine profiles, and histology. Results: Coated silicone breast implants demonstrated a color change, increased mass, and Fourier transmission infrared spectroscopy consistent with a doxycycline coating. Coated implants were nontoxic to fibroblasts and inhibited biofilm formation and bacterial adherence after MRSA and P. aeruginosa incubation in vitro, and measurable doxycycline concentrations at 24 hours were seen. In a mouse model, a significant reduction of MRSA and P. aeruginosa bacterial colonization after 3 and 7 days in the doxycycline-coated implant mice was demonstrated when compared to the control mice, control mice treated with intraperitoneal doxycycline, and control mice treated with a gentamicin/cefazolin/bacitracin wash. Decreased inflammatory cytokines and inflammatory cell infiltration were demonstrated in the doxycycline-coated mice. Conclusions: A method to coat silicone implants with doxycycline was developed. The authors' doxycycline-coated silicone implants significantly reduced biofilm formation, surgical-site infections, and inflammation. Further studies are needed to evaluate the long-term implications. Abstract : Supplemental Digital Content is available in the text.